A sign of affection. 4 - Dashiell, Christine, 1984- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2021)
"Yuki, a deaf college student who's led a relatively sheltered life, has just taken a huge step: She's got a boyfriend! And he seems like a keeper: Itsuomi is a multilingual globetrotter who works hard, and he's a knockout, to boot. Yuki can still scarcely believe that Itsuomi casually dropped the question, 'Wanna go out with me?' And she can't help wondering, when will Itsuomi start to open up to her about his past, and his dreams for the future? Is this a whim, or is it real?"--